Pulmonary artery sarcoma and severe valvular diseases in late-septuagenarian women: was 2-stage surgery an appropriate strategy? A case report - Sakiko Sato; Hideo Ichimura; Keisuke Kobayashi; Shuntaro Kawabata; Tomoyuki Kawamura; Hisashi Suzuki; Akito Imai; Kanji Matsuzaki; Akiko Sakata; Daisuke Matsubara; Yukio Sato (Surgical Case Reports)
Abstract Background Pulmonary artery sarcomas (PASs) are rare, and complete tumor resection is often difficult at the time of detection. We encountered a case of PAS that was thought to be resectable; however, the patient had severe symptomatic valvular disease. We faced a difficult decision regarding the surgical strategy. Case presentation A 76-year-old female presented with a history of polysurgery for multiple primary cancers. She was referred to our department with a calcified mass in the right pulmonary artery (PA) and severe symptomatic valvular disease. After a discussion with the cardiovascular surgeon, we decided to perform a two-stage surgery. She underwent valvuloplasty through a median sternotomy, resulting in an improvement in her exertional dyspnea. The tumor was removed three months later with a right upper lobectomy and PA patch reconstruction through a posterolateral thoracotomy. When the PA was opened, the edge of the tumor was entrapped by vascular clamp forceps because of insufficient dissection of the adhesions between the superior vena cava and the right main PA resulting from the first operation. The patient underwent proton therapy twice for chest wall metastases which recurred three months after surgery, and local recurrence in the PA was diagnosed five months after surgery. The patient was alive with stable disease 25 months after surgery. Conclusion Two-stage surgery for PAS and valvular disease resulted in incomplete resection of the PAS in the right PA. It is important not to underestimate surgical adhesions due to the initial surgery and to consider and implement measures to prevent adhesions of critical vessels during the second operation.